ISOLATION OF Micractinium Pusillum FRESENIUS FROM FISH PONDS USING SDE TECHNIQUES: SEDIMENTATION, DILUTION, AND ENRICHMENT - Adam, Chaidir; Haryono, Agus; Purnaningsih, Titin; Araina, Elga; Mashabhi, Sugeng; Velina, Yessy; Fatiqin, Awalul (LPPM Universitas Jambi, 2025)
Green water in fish ponds, caused by algal blooms, harbors a diverse array of microalgae species and is commonly observed in aquaculture settings. This resource-rich water source holds promise for research focused on microalgae cultivation at a laboratory scale, serving as a valuable starter sample for such investigations. Preliminary observations suggested that the predominant species in such green water habitat belonged to the genus Micractinium Fresenius 1858. An effective isolation technique of this microalgae species is necessary, not only to reduce the contamination of the rotifers but also to purify the starter cultures. Although automated microalgae isolation techniques have been developed recently, such as using Flow Cytometry via Cell Sorting, traditional isolation techniques are still relevant. One of the traditional microalgae isolation techniques that has been widely used for many years is the dilution technique. This study aims to isolate Micractinium pusillum Fresenius from fish ponds using the modified dilution technique: SDE (sedimentation, dilution, and enrichment). The dilution results showed that rotifer contamination was reduced at a dilution of 10─3 and the density of microalgae was also reduced. At this dilution level, only one type of microalgae was observed, i.e., Micractinium pusillum Fresenius. which was then cultured for enrichment using a simple photobioreactor. This 10-3 culture was observed to grow well during the enrichment stage for 10 days. These results indicate that the SDE isolation technique can be effectively used to isolate microalgae from green water, especially for Micractinium pusillum which is the most abundant microalgae species in green water in this study.